Cardiac conduction abnormalities and congenital immunodeficiency in a child with Kabuki syndrome: Case report - deMello Daphne E; Mavers Melissa; Bogucki Brian; Shah Maulik; Knutsen Alan (BMC, 2005)
Abstract Background Since it's recognition in 1981, a more complete phenotype of Kabuki syndrome is becoming evident as additional cases are identified. Congenital heart defects and a number of visceral abnormalities have been added to the typical dysmorphic features originally described. Case Report In this report we describe the clinical course of a child diagnosed with Kabuki syndrome based on characteristic clinical, radiological and morphologic features who died of a cardiac arrhythmia at 11-months of age. This infant, however, had abnormal pulmonary architecture and alterations in his cardiac conduction system resulting in episodes of bradycardia and asystole. This child also had an immunological phenotype consistent with common variable immunodeficiency. His clinical course consisted of numerous hospitalizations for recurrent bacterial infections and congenital hypogammaglobulinemia characterized by low serum IgG and IgA but normal IgM levels, and decreased antibody levels to immunizations. T-, B- and NK lymphocyte subpopulations and T-cell function studies were normal. Conclusion This child may represent a more severe phenotype of Kabuki syndrome. Recurrent infections in a child should prompt a thorough immunological evaluation. Additionally, electrophysiology testing may be indicated if cardiopulmonary events occur which are not explained by anatomic defects.